2022
DOI: 10.1097/naq.0000000000000502
|View full text |Cite
|
Sign up to set email alerts
|

The Seniority Swoop

Abstract: We sought to understand whether nurses aged 20 to 29 years burnout and intend to turnover in higher proportions than more senior nurses, and if so, why. Guided by Maslow's hierarchy, we used brief inventories to assess hospital-based bedside nurses at 11 hospitals in Pennsylvania and Rhode Island (n = 3549/9520) prior to the pandemic. In a second study, we compared scheduling policies, bargaining, and Magnet status to see whether these variables predicted worsened burnout rates in young nurses. In a pattern th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 48 publications
(74 reference statements)
0
0
0
Order By: Relevance
“…The logistical regression reinforced these findings. It also reinforced the idea that workers with higher seniority are less exposed to WPV, consistent with several other studies [26,38,39]. Studies have shown that professional experience improves the ability to manage conflict situations with angry patients [10].…”
Section: Discussionsupporting
confidence: 87%
“…The logistical regression reinforced these findings. It also reinforced the idea that workers with higher seniority are less exposed to WPV, consistent with several other studies [26,38,39]. Studies have shown that professional experience improves the ability to manage conflict situations with angry patients [10].…”
Section: Discussionsupporting
confidence: 87%
“…The majority of participants reported rarely being treated with courtesy and respect by coworkers, highlighting a prevalent issue of workplace disrespect. This aligns with previous research indicating that lateral violence is a common issue in nursing, contributing to a stressful and hostile work environment (10)(11)(12)(13).…”
Section: Discussionsupporting
confidence: 91%
“…This phenomenon creates a toxic work environment, contributing to increased stress, job dissatisfaction, and potentially compromising patient care (6)(7). It is crucial to address lateral violence effectively to improve the overall healthcare environment and ensure the well-being of both healthcare providers and patients (8)(9)(10)(11)(12)(13). This study aims to assess the prevalence and causes of lateral violence among nurses at Jinnah Hospital Lahore.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study carried out during the Covid-19 pandemic in healthcare workers, it was observed that seniority lowers the chance of being exposed to WPV (Dopelt et al, 2022). Numerous studies show that professional experience improves the ability to manage conflict situations with angry patients (Li et al, 2018;Shapiro et al, 2022;Sharipova et al, 2010).…”
Section: Differences Between Seniority Groupsmentioning
confidence: 99%